Detection and analysis of human hemoglobin HB and HBO2 with new Nano-sensor based on chiral metamaterials - Zinelabiddine, Mezache; ZARA, Chemseddine; LARIOUI, Fateh; Benabdelaziz, Fatiha (International Journal of Physical Research, 2017)
This article is devoted to the simulation COMSOL Multiphysics of ultra-sensitive nano-sensor based on chiral Metamaterials, which allows us to follow hemolysis with good accuracy. Where we will study the reflected wave in human hemoglobin oxygenated and deoxygenated to determine its concentration. In this paper we also present the numerical results and the equations of variations obtained by Matlab.